3-D WAVE PROPAGATION ANALYSIS TO DETERMINE SCALING FACTOR AND BASIN EFFECT ON 1-D WAVE PROPAGATION ANALYSIS - Kurnia Jayanti, Harum
The basin effect is known to have influences on the earthquake response at the ground surface, especially at the edge of basin and will cause amplification of seismic waves in soft sediment deposits. The geometry of the basin greatly influences the resulting basin effect because the basin’s slope will trap body waves and cause stronger and longer earthquakes. The common 1-D and 2-D analyses often fail to accurately capture the complex geometries, and spatial variations present in such environments, leading to insufficient predictions of seismic responses. The research investigates the behavior of soil responses through a series of 3-D simulations, emphasizing the importance of accurately modeling seismic wave propagation in basin. Key objectives include evaluating soil behavior under varying seismic loads inside the basin, understanding the amplification effects caused by basin geometries, and deriving a practical scaling factor from the comparative analysis between 1-D and 3-D models. Results indicate that 3-D wave propagation models provide a more reliable representation of ground shaking phenomena than their 1-D counterparts, particularly at basin edges. This study ultimately aims to enhance site response analysis methodologies by emphasizing the necessity for incorporating scaling factors in seismic assessments to improve accuracy in predicting ground shaking responses, thereby contributing valuable insights for geotechnical engineering practices in earthquake – prone regions.